ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP PROFITABILITAS PERBANKAN (Studi pada Bank Umum di Indonesia Periode Januari 2003 - Februari 2012) - Hendrayanti, Silvia; Muharam, Harjum (Diponegoro Journal of Management, 2013)
Bank is one of the financial institution which have activities to raise funds from the public inthe form of savings and channel them to the public in form of credit or other forms in order toimprove the living standard of the people. The purpose of the banking business to make a profitability.The bank profitability is one of the most important indicator in determining the success of a bank andcan be used as basis for policy and strategy of the banking system in the period to come. The mainpurpose of this research is to examine the influence of Equity to Total Assets Ratio (EAR), OperatingExpenses to Operating Income (ROA), Loan to Assets Ratio (LAR), Firm size, economic growth,inflation and the volatility of ROA on Return On Assets (ROA).The population of this research are commercial banks in Indonesia. The priority selection ofthe sample is by using purposive sampling method with the overall criteria of the monthly financialreports of the most commercial bankings in Indonesia during the observation period January 2003-February 2012 has been published by Bank Indonesia. Totality of the sample which has been used inthis study was 110 samples. In this study, the research method is by using descriptive analysis,stationarity test, classical assumption test (test for normality and autocorrelation test), analyticalmodels of the Generalized Autoregressive Conditional Heteroscedasticity in Mean (GARCH-M),hypothesis test (z-statistic test, F-statistics test, and coefficient of determination test (R2)).The results of this research found that Equity to Total Assets Ratio (EAR) have a positive andsignificant effect on Return on Assets (ROA), Operating Expenses to Operating Income (ROA) andLoan to Assets Ratio (LAR) have a negative and significant effect on Return On assets (ROA), Firmsize have a positive and significant effect on Return on Assets (ROA), economic growth and inflationhave regression coefficients were positive but insignificant ROA and volatility of ROA have anegative and significant effect on Return On asset (ROA).